The population of Galactic Centre filaments - III. Candidate radio and stellar sources - Yusef-Zadeh, F; Arendt, RG; Wardle, M; Heywood, I; Cotton, W (Oxford University Press, 2022)
Recent MeerKAT radio continuum observations of the Galactic Centre at 20 cm show a large population of non-thermal radio filaments (NRFs) in the inner few hundred pc of the Galaxy. We have selected a sample of 57 radio sources, mainly compact objects, in the MeerKAT mosaic image that appear to be associated with NRFs. The selected sources are about four times the number of radio point sources associated with filaments than would be expected by random chance. Furthermore, an apparent correlation between bright IR stars and NRFs is inferred from their similar latitude distributions, suggesting that they both co-exist within the same region. To examine if compact radio sources are related to compact IR sources, we have used archival 2MASS, and Spitzer data to make spectral energy distribution of individual stellar sources coincident or close to radio sources. We provide a catalogue of radio and IR sources for future detailed observations to investigate a potential three-way physical association between NRFs, compact radio and IR stellar sources. This association is suggested by models in which NRFs are cometary tails produced by the interaction of a large-scale nuclear outflow with stellar wind bubbles in the Galactic Centre.